Review Probable Ingredients for Trans Free Margarine with Omega-3 Fatty Acids: Review: Trans Free Margarine and Omega-3 Fatty Acids (Biological Sciences - PJSIR, 2018)
Margarine is widely used as table spread, in cooking and bakery products. Awareness of consumers regarding the intake of omega fatty acids has led the food industry to develop foods which are rich sources of omega fatty acids. Harmful effects of trans on the development of cardiovascular diseases have steered the researchers to find out wide range of trans free options, without compromising on functional and physical properties of fats. Nutritionists recommend margarine for the growing and school going babies, it is usually manufactured from the combination of hard and soft fats, followed by the addition of vitamins A, D and E. However, little is known regarding the supplementation of margarines with omega fatty acids of chia oil. This paper summarizes the physical and chemical characteristics of few ingredients that may be  used  in  the  formulation  of  trans  free  margarine  with  higher  magnitude  of  omega  fatty  acids.